Human health effects of recycling and reusing food sector consumer plastics: A systematic review and meta-analysis of life cycle assessments. (15th April 2023) - Deeney, Megan; Green, Rosemary; Yan, Xiaoyu; Dooley, Claire; Yates, Joe; Rolker, Heike B.; Kadiyala, Suneetha
Abstract: Global transitions to circular economies of plastic could pose both risks and opportunities for human health. Life Cycle Assessment (LCA) can help to quantify possible health effects across plastic life cycles, syntheses of which could inform policy. This systematic review assessed LCA evidence for health effects of increased plastic recycling and reuse in the food sector. Scientific databases including Web of Science, Scopus, MEDLINE, Embase, Global Health, GreenFile and grey literature websites were searched for peer-reviewed LCA of consumer-level food sector plastics that compared virgin or single-use plastics with scenarios of increased recycling and reuse. Data on Human Health impacts and related midpoint impacts were extracted, converted to Disability-Adjusted Life Years (DALYs), and analysed using meta-regression. Forty-nine eligible LCAs were identified, only five of which related to low- and middle-income countries (China: n = 1 and Thailand: n = 4). Meta-regression showed strong evidence for a linear trend in reducing DALYs with increasing percentage recycled content compared to virgin plastic (Coefficient = −1.96E-5; 95% CI = −2.69E-5 to −1.24E-5; p < 0.0001) and increasing end-of-life recycling rate compared to landfill and/or incineration (Coefficient = −2.1E-5; 95% CI = −2.60E-5 to −1.63E-5; p < 0.0001), equating to almost a day of healthy life saved globally per tonne of plastic recycled. On average, reusable plastics reduced climate-related health impacts associated with single-use plastics after 30 uses. Global assessment was limited by data deficits, but meta-analyses suggested that health risks from linear economies of food sector plastics could be reduced by increasing recycling and reuse rates, though some reusable plastics would need to be used many more times than current norms. Encouraging greater geographical coverage in LCA, increasing uptake of health impact assessment methods, and incorporating emerging health data will strengthen future public health evaluations of circular economies. Highlights: Health risks of plastic linear economies could be reduced by increasing recycling. On average, reusable plastics yielded health benefits over single-use after 30 uses. Life cycle assessment syntheses support analyses of circular economy health effects. Health pathways remain poorly understood and underutilised in modelling circularity. Low- and middle-income countries are underrepresented in life cycle assessments.